Effect of signal peptide alterations and replacement on export of xylanase A in Streptomyces lividans. - Pagé, N (1996)
Starting from its translation initiation site, the Streptomyces lividans xylanase A signal peptide consists of 41 amino acids. This signal peptide was deleted and successively replaced with one of six signal peptides from other enzymes secreted by S. lividans and by a signal peptide from the outer membrane protein (LamB) of Escherichia coli. Deletion of the xylanase A signal peptide or modification of its cleavage site abolished secretion of the enzyme. Replacement with the signal peptides of either xylanase B, cellulase A, mannanase, or acetylxylan esterase produced equivalent amounts of xylanase A, while the signal peptides of cellulase B, xylanase C, and LamB secreted less enzyme than did the wild type. All the clones exhibited the same transcription levels, which indicated that the variations in xylanase production were due to the natures of the signal sequences.